2015
DOI: 10.1002/jmri.24830
|View full text |Cite
|
Sign up to set email alerts
|

Placental perfusion in uterine ischemia model as evaluated by dynamic contrast enhanced MRI

Abstract: Background To validate DCE MRI method of placental perfusion estimation and to demonstrate application of the method in a rabbit model of fetal antenatal hypoxia-ischemia. Methods Placental perfusion was estimated by dynamic contrast imaging with bolus injection of Gd-DTPA in 3 Tesla GE magnet in a rabbit model of placental ischemia–reperfusion in rabbit dams at embryonic day 25 gestation age. Placental perfusion was measured using steepest slope method on DCE MRI before and after intermittent 40 min uterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Animal DCE MRI, the technique that we chose, has been recently used in studies to investigate pathological models [19, 23]. Placental perfusion has also been studied by techniques other than DCE in humans, such as arterial spin labeling and intravoxel incoherent motion [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal DCE MRI, the technique that we chose, has been recently used in studies to investigate pathological models [19, 23]. Placental perfusion has also been studied by techniques other than DCE in humans, such as arterial spin labeling and intravoxel incoherent motion [13].…”
Section: Discussionmentioning
confidence: 99%
“…DCE MRI was chosen to study placental function in this model: it is a robust method for assessing placental perfusion, and has been used successfully in several studies [5, 8, 12, 19-23]. Our results for the control group were similar to those reported in the literature under normal conditions, with a mean placental blood flow of 140–149 mL/min/100 mL, in accordance with previous results obtained with DCE MRI [5-8, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Iran-Nejad et al [8] found the uterus weight augmented by estradiol (P<0.05) after renal IR injury in female rats. Drobyshevsky et al [9] showed a significant 3.72-fold hypoperfusion of the maternal…”
Section: Journal Of Contraceptive Studies Issn 2471-9749mentioning
confidence: 97%